Characterization of CO1 and 18S rDNA genes from Indonesian native ornamental shrimp Caridina boehmei cultured in Jakarta - Ekky Ilham Romadhona; Novi Megawati; Handang Widantara; Sutanti Sutanti; Arif Rahman Ardiansyah; Kiki Mariya Dewi; Annisa Fitri Larassagita; Aditia Firman; Moh Risky; Rahmat Rahmat; Ayub Ayub (Jurnal Akuakultur Indonesia)
Caridina boehmei is an ornamental shrimp native to Sulawesi that has been successfully cultured and marketed in Indonesia. However, molecular information about this shrimp is not yet available. This study aimed to characterize cytochrome c oxidase subunit I (CO1) and small subunit ribosomal RNA (18S rDNA) genes. Shrimp samples were extracted, and DNA was amplified using CO1 and 18S rDNA primers. The sequencing results were then analyzed by the neighbor-joining method. The 654 bp partial coding sequence (cds) of the CO1 and 380 bp partial cds of 18S rDNA have been successfully amplified from genomic DNA. The CO1 sequencing produced fragments consisting of 25.84% adenine, 20.95% cytosine, 19.11% guanine, and 34.10% thymine. The 18S rDNA sequencing produced fragments consisting of 24.47% adenine, 26.05% cytosine, 28.16% guanine, and 21.32% thymine. Phylogenetic analysis based on the CO1 gene revealed that C. boehmei was grouped with C. variabilis (MK190014), C. brachydactyla (MK190011), and Caridina sp. (MK190012). Phylogenetic analysis based on the 18S rDNA gene revealed that C. boehmei was identical to Caridina sp. Suphan Buri-1 MF622000, C. serratirostris KP725708, C. multidentata JF346236, C. formosae GQ131924, and Caridina sp. Suphan Buri-2 MF622001. The lowest-highest pairwise distance based on CO1 and 18S rDNA was consecutively 0.0017-0.2247 (0.17-22.47%) and 0.0000-0.1218 (0-12.18%).